Study Imbalance of Some Cytokines and Vaginitis Agents in Women with Recurrent Abortion Women - Muna Hamid Al-sallami; Samara Abd Al-Hameed Ouda Al-Salihi; Mayyada Farhan Darweesh (Medical Journal of Babylon)
Background: Cytokines play a key role in the success or failure of pregnancy. On the other hand, a plethora of bacterial and viral infectious agents have been associated with an increased risk of recurrent abortion (RA). Objective: This search focused on the association between cytokines imbalance and vaginitis infection with RA cases. Materials and Methods: A case-control study was designed on 65 aborted women attending AL-Hakeem Hospital in AL-Najaf province suffering from at least two or more aborting cases and 40 healthy delivery women as the control group. Two milliliters of blood samples were collected from all participants to measure interleukin-17 (IL-17), interleukin-23 (IL-23), and interleukin-10 (IL-10) levels by enzyme-linked immunosorbent assay (ELISA). High vaginal swabs were taken from all patients, cultured on differential media for 24 h at 37°C, and then positive bacterial growth re-culturing to obtain a pure single colony. Results: The results showed that the mean age of aborted women was 29.8 vs 27.4 years, and 33% have a positive family history; according to bacterial infection, the results found that positive bacterial growth appeared in 23 (35.3%) of high vaginal swabs (HVSs), while 42 (64.7%) gave negative results. The prevalence of bacteria was as follows: E. coli was isolated from 8/23 (34.8%) patients, followed by P. aeruginosa from 6/23 (26.0%). The results confirmed that IL-17 and IL-23 were higher in aborted women (126.4 ± 34.8, 84.9 ± 23.7 pg/ml) compared to delivered women (37.5 ± 11.2, 26.8 ± 9.6 pg/ml). Also, infected women had highly elevated levels of both cytokines (180.2 ± 28.5, 104.7 ± 43.4 pg/ml) compared to non-infected women (72.8 ± 24.9, 67.3 ± 18.5 pg/ml), while IL-10 decreased in aborted women compared to healthy women. Conclusion: Cytokines imbalance leads to impaired state of pregnancy, and there is a highly significant relationship between IL-17, IL-23, and IL-10 levels with abortion, especially in women who suffer from bacterial vaginitis